Faktor yang Mempengaruhi Tingkat Kepatuhan Pedagang Menerapkan Protokol Kesehatan COVID-19 di Pasar Tradisional - Fitasari, Putri; Pawenang, Eram Tunggul (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: WHO has declared a global emergency due to the outbreak of COVID-19 since January 2020. Traditional markets are a category of places that are vulnerable to transmission because market conditions are public facilities and many people are active in these locations. The purpose of this study is to determine factors related to the implementation of health protocols - 19 on traders in Traditional Markets. Methods: This type of research is quantitative analytic with a cross sectional design, with the research subject being traditional market traders. The sampling technique applied was proportional random sampling. The research instruments used were observation sheets, questionnaire sheets and cameras. Bivariate data analysis using chi square statistical test. Result: The results showed that there was a relationship between the level of knowledge of the COVID-19 Health Protocol p-value 0.031, the attitude level of the COVID-19 Health Protocol p-value 0.037, the personal hygiene level of traders p-value 0.001 with compliance with the implementation of the COVID-19 Health Protocol. Conclusion: The need to complete sanitation facilities, especially hand washing facilities. More actively socializing health protocols, routine inspections related to sanitation, and conducting indirect counseling methods through social media and print media.